Figure 2 in Diet of the European eel Anguilla anguilla (Linnaeus, 1758) in two transitional waters of Southwestern Mediterranean - Derbal, Farid; Hamdi, Sandra; Rouag-Laouira, Lydia; Chaoui, Lamya; Kara, Mohamed Hichem (Zenodo, 2022)
Figure 2. – Evolution of the digestive vacuity coefficient (Cv %) of Anguilla anguilla according to season and development stages in Mellah lagoon (in black) and Wadi El Kebir (in gray). The values above the bars mean the number of eels examined. Published as part of Derbal, Farid, Hamdi, Sandra, Rouag-Laouira, Lydia, Chaoui, Lamya & Kara, Mohamed Hichem, 2022, Diet of the European eel Anguilla anguilla (Linnaeus, 1758) in two transitional waters of Southwestern Mediterranean, pp. 3-11 in Cybium 46 (1) on page 5, DOI:10.26028/cybium/2022-461-001, http://zenodo.org/record/10836082